Collaborative Governance Dalam Pelaksanaan Program East Java Super Coridor Pada Badan Kooordinasi Wilayah IV Pamekasan - Basyarahil, Abubakar; Abdurrahman, Abdurrahman; Sari, Dwi Novita (Assyarikah: Journal of Islamic Economic Business, 2025)
This study aims to examine the effectiveness of collaboration between stakeholders in the EJSC program implemented by the Pamekasan Regional Coordination Agency (Bakorwil) IV. This study uses the collaborative governance theory developed by Chris Ansell and Alison Gash with four main indicators: starting conditions, institutional design, facilitative leadership, and collaborative process. The research method used is a qualitative approach with the research location at Bakorwil IV Pamekasan. Data were obtained through in-depth interviews and documentation, using a purposive sampling technique, and analyzed using the Miles and Huberman interactive model that includes data collection, data condensation, data presentation, and drawing conclusions. The study shows that synergy between the government and the private sector has been established, but community participation is low and the institutional design is unclear. Facilitative leadership is effective through mediation and empowerment, although understanding of objectives is not yet evenly distributed. This program is beneficial for MSMEs and reducing unemployment. These findings strengthen the practice of collaborative governance in regional public policy.